Partial response to niraparib in combination with tislelizumab in a patient with metastatic undifferentiated tonsillar carcinoma: a case report and literature review - Zhang, Jing; Dai, Zi; Liao, Pei; Guan, Jieshan (Frontiers in Oncology, 2023)
Undifferentiated tonsillar carcinoma is an extremely rare head and neck cancer. The treatment options are challenging due to insensitivity to chemotherapy and easy development of drug resistance. In this study, we reported a case of advanced undifferentiated tonsillar carcinoma with multiple mediastinal lymph node metastases that failed to respond to chemotherapy. Next-generation sequencing (NGS) revealed germline BReast CAncer gene (BRCA) 1 mutation and a high tumor mutational burden. Poly (adenosine diphosphate [ADP]-ribose) polymerase (PARP) inhibitors have demonstrated efficacy in solid tumors with BRCA1/2 mutations. Immune checkpoint inhibitors (ICIs) provide a treatment option for unresectable head and neck cancer. After local control treatment by embolization, niraparib and tislelizumab were administered to this patient. A partial response (PR) was achieved, and progression-free survival (PFS) and overall survival (OS) were 12 months and 19 months, respectively. This case reveals molecular profiling as an important therapeutic strategy for rare malignancies with no standard of care. Moreover, the underlying synergistic antitumor activity of PARPi and PD-L1 blockade was reviewed.